Edición y comunismo : Cultura impresa, educación militante y prácticas políticas (México, 1930-1940) - Rivera Mir, Sebastián (Serie Historia y ciencias sociales., 2020)
"For many militants on the left, an important part of their activities take place around publishing. Learning to use the mimeograph, hand out books, write articles, sell brochures, distribute loose sheets, among many other practices, have accompanied the left throughout its history. This work seeks to reconstruct a fragment of that past. In particular, it focuses on the challenges that Mexican Communist militants faced in the 1930s to push their own issues. In the different chapters, the reader will find everything from everyday aspects, government censorship, to transnational editorial dynamics, through disputes with anti-communism or the epic actions of militants who found in the printed matter a way to make the revolution. The subjects involved sought to endow "theory with practice". In short, this book analyzes, from a novel perspective, how that effort reconfigured not only their daily lives, but also the scope of their own political project"--